Recent Update on Retinoic Acid-Driven Initiation of Spermatogonial Differentiation - Bhattacharya, Indrashis; Sharma, Partigya; Purohit, Shriya; Kothiyal, Sachin; Das, Moitreyi; Banerjee, Arnab (Frontiers in Cell and Developmental Biology, 2022)
Germ cells (Gc) propagate the genetic information to subsequent generations. Diploid (2n) Gc get transformed to specialized haploid (n) gametes by mitotic and meiotic divisions in adult gonads. Retinoic acid (RA), an active derivative of vitamin A (retinol), plays a critical role in organ morphogenesis and regulates the meiotic onset in developing Gc. Unlike ovaries, fetal testes express an RA-degrading enzyme CYP26B1, and thereby, male Gc fail to enter into meiosis and instead get arrested at G0/G1 stage, termed as gonocytes/pro-spermatogonia by embryonic (E) 13.5 days. These gonocytes are transformed into spermatogonial stem/progenitor cells after birth (1–3 days of neonatal age). During post-natal testicular maturation, the differentiating spermatogonia enter into the meiotic prophase under the influence RA, independent of gonadotropic (both FSH and LH) support. The first pulse of RA ensures the transition of undifferentiated type A spermatogonia to differentiated A1 spermatogonia and upregulates STRA8 expression in Gc. Whereas, the second pulse of RA induces the meiotic prophase by augmenting MEIOSIN expression in differentiated spermatogonia B. This opinion article briefly reviews our current understanding on the RA-driven spermatogonial differentiation in murine testes.